Complete thoracoscopic excision of an infected bronchogenic cyst due to mediastinitis - Kim, Yong Hwan; Kim, Jae Jun; Choi, Si Young; Jeong, Seong Cheol; Kim, In Sub (Journal of Thoracic Disease; Vol 9, No 11 (November 29, 2017): Journal of Thoracic Disease (Quantitative Imaging of Thoracic Diseases), 2017)
Because bronchogenic cysts can result in infection, further complications due to compression of adjacent organs or malignant transformation, symptomatic and complicated bronchogenic cysts are usually surgically removed. However, surgical excision can be hazardous or incomplete because of dense adhesion to surrounding vital organs as a consequence of severe inflammation. Herein, we report a rare case of infected bronchogenic cyst caused by mediastinitis and we describe how a surgical approach using video-assisted thoracoscopic surgery (VATS) should be considered for treatment, even among patients with complicated bronchogenic cysts.